Ain Ni Ain dalam Kerukunan Antarumat Beragama di Kepulauan Kei - Nana Mardiyah Renhoat; Trie Yunita Sari (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
In social life, of course there is a philosophy of life that is born from local wisdom which becomes the identity of the community itself. However, as time progressed, this philosophy began to be eroded and considered backward, making it possible for society to no longer defend it as a philosophy of life. This research explains how Ain Ni Ain which is the philosophy of life of the Kei people, can play a role and function in creating harmony and how Ain Ni Ain can survive in the life of Kei society. As a result, Ain Ni Ain is an important life philosophy of the Kei community which plays a role in creating harmony between religions believers based on fraternal relations. Apart from that, this proves that Ain Ni Ain can survive following the needs of its people, because the Kei people are able to make various efforts so that this philosophy can survive and be maintained.